2021
DOI: 10.3390/ijms22094454
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite as a Biomaterial for Peripheral Nerve Regeneration after Mechanical Damage—In Vitro Study

Abstract: Hydroxyapatite has been used in medicine for many years as a biomaterial or a cover for other biomaterials in orthopedics and dentistry. This study characterized the physicochemical properties (structure, particle size and morphology, surface properties) of Li+- and Li+/Eu3+-doped nanohydroxyapatite obtained using the wet chemistry method. The potential regenerative properties against neurite damage in cultures of neuron-like cells (SH-SY5Y and PC12 after differentiation) were also studied. The effect of nanoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Benita Wiatrak et al [64] showed that nanohydroxyapatite molecules can also induce nerve regeneration. There is an interaction between the time of nerve inflammation and an increase in the activity of mitochondria in neurons affected by hydroxyapatite nanoparticles.…”
Section: Hydroxyapatite (Hap)mentioning
confidence: 99%
“…Benita Wiatrak et al [64] showed that nanohydroxyapatite molecules can also induce nerve regeneration. There is an interaction between the time of nerve inflammation and an increase in the activity of mitochondria in neurons affected by hydroxyapatite nanoparticles.…”
Section: Hydroxyapatite (Hap)mentioning
confidence: 99%
“…Taking advantage of the properties of conductive and biodegradable polymers, their scaffold was designed to promote directional axonal growth and migration of Schwann cells via the microstructure of the biodegradable polymer fibers [ 26 ]. In addition, a recent study by Wiatrak et al 2021, showed that nanocrystalline apatite doped and co-doped with Li + and Eu 3+ ions might be a very attractive biomaterial for the regeneration of nervous tissue, where europium ions influence neuronal features even more strongly than doping with lithium alone [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the properties of conductive and biodegradable polymers, their scaffold was designed to promote directional axonal growth and migration of Schwann cells via the microstructure of the biodegradable polymer fibers [22]. Also, a recent study of Wiatrak et al 2021, showed that nanocrystalline apatite doped and co-doped with Li + and Eu 3+ ions may be a very attractive biomaterial for the regeneration of nervous tissue, where europium ions influence neuronal features even more strongly than doping with lithium alone [23].…”
Section: Introductionmentioning
confidence: 99%